H_∞ based anti-windup controller for two-dimensional discrete delayed systems in presence of actuator saturation. (11th January 2017) - Chandra Pal, Vipin; Negi, Richa
Abstract: This article addresses the problem of stability analysis for a class of two-dimensional discrete systems described by Roesser model in the presence of actuator saturation and interval-like time varying state delay. The dynamic output feedback H_∞ stabilization controller appended with an anti-windup compensator is used. The saturation nonlinearity is tackled using sector conditions. Sufficient conditions for asymptotic stability in terms of linear matrix inequality (LMI) are derived using Lyapunov–Krasovskii functional and the domain of attraction is also estimated for the system under consideration. Some examples are provided to illustrate the effectiveness of the proposed approach.